P055 Mechanisms Underlying Sleep Disturbance in Young People with Borderline Personality Disorder Features. (7th October 2021) - Jenkins, C; Thompson, K; Nicholas, C; Chanen, A
Abstract: Introduction: Sleep problems are common in young people (aged 15–25 years) with features of borderline personality disorder (BPD). Yet the mechanisms underlying this relationship remain largely unknown. This study explored the indirect roles of emotion regulation difficulties, depression, anxiety and stress in the relationship between BPD features and sleep disturbance in young people. Method: Sleep was measured subjectively (self-report) and objectively (10 days wrist actigraphy) in 40 young people with BPD features (36 females, Mage = 19.77, SD = 2.51) and 38 healthy young people (34 females, Mage = 20.06, SD = 2.52). Participants also completed the Difficulties in Emotion Regulation Scale and the Depression, Anxiety and Stress Scale. Results: Mediation analyses revealed that impulse control difficulties, limited access to emotion regulation strategies, and anxiety played an indirect role in subjective sleep disturbances in young people with BPD features. Lack of emotional awareness and anxiety indirectly contributed to associations between BPD features and objectively longer time in bed and bedtime variability, respectively. Discussion: Targeting impulse control difficulties, emotion regulation strategies and anxiety through improving impulse control, improving emotion regulation skills and reducing pre-sleep arousal might be beneficial for improving subjective sleep in this population. Similarly, improving emotional awareness and reducing anxiety might help to normalise objective sleep patterns. Overall, these findings help to guide the development of targeted sleep-improvement strategies that might serve as useful adjuncts to current interventions for young people with BPD features.